Principles of capitalistic commodity production reconsidered - Jens Reich (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2013)
Helmedag (2012) derives effects on employment caused by changes in (a) uncompensated wage hours, (b) output, (c) productivity, and (d) a combination of the latter two. His results are derived from a linear two-sector model. His closure of the model is based on the determination of the profit rate via aggregate production. This closure bears some flexibility. Changes in the profit rate require changes in the composition of output, but the level of total production cannot be derived uniquely thereof. It will be shown, therefore, that results (a), (c) and (d) depend on a specific assumption. Without it, different adjustment paths are possible. The model is then either limited to economies of certain institutional characteristics, or a plea for certain institutional elements, such as social insurance systems.
Keywords: A10; B12; E10; 330; effective demand; employment; income shares; rate of profit